1998
DOI: 10.1046/j.1365-2362.1998.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for an increase in thrombopoiesis after liver transplantation

Abstract: Our findings provide direct evidence for an increase in de novo platelet production after orthotopic liver transplantation. As the elevation of reticulated platelets precedes platelet recovery, it could serve as an early indicator to predict thrombopoiesis as a result of reconstituted liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
1
19
2
Order By: Relevance
“…These data suggest that concentration of serum TPO is, to some degree, dependent on the capacity of the liver to produce this protein. Since liver function in patients who underwent orthotopic liver transplantation seemed to be severely impaired [20][21][22][23], the discrepancy between the results of this study and ours may derive from difference in severity of liver dysfunction.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…These data suggest that concentration of serum TPO is, to some degree, dependent on the capacity of the liver to produce this protein. Since liver function in patients who underwent orthotopic liver transplantation seemed to be severely impaired [20][21][22][23], the discrepancy between the results of this study and ours may derive from difference in severity of liver dysfunction.…”
Section: Discussioncontrasting
confidence: 89%
“…Hepatoma cells also express TPO mRNA [18,19]. Indeed, it is reported that serum TPO was low in liver cirrhosis but, however, it was increased after orthotopic liver transplantation, which was followed by an increase in platelet count [20][21][22][23]. These observations may support the hypothesis that impaired production of TPO in liver disease contributes to thrombocytopenia associated with chronic viral hepatitis.…”
Section: Introductionmentioning
confidence: 83%
“…Cirrhotic patients have a lack of TPO relative to their platelet counts, as evidenced by the approximately 10-fold higher serum TPO concentration in similarly thrombocytopenic patients with aplastic anemia. 10,20,21 In addition, Martin et al 9 and Stiegler et al 22 showed that circulating TPO increases in adult patients with cirrhosis after orthotopic liver transplantation, reaching a maximum 5 to 6 days after surgery. This increase has been related to the potential of the transplanted liver to produce TPO.…”
Section: Discussionmentioning
confidence: 99%
“…For rescuing patients from these disorders, direct removal of spleen by splenectomy (Puttini et al 1979; Soper & Rikkers 1982), volume reduction of spleen by partial splenic embolization (Stiegler et al 1998; Sangro et al 1993; Herrero et al 1997), or portal decompression by transjuglar intrahepatic portosystemic shunt (Alvarez et al 1996; Pursnani et al 1997) are performed as the effective methods in these days. However, some controversial reports have noted that thrombocytopenia may persist even after splenectomy or partial decompression (Pradella et al 2011; Sanyal et al 1996; Gschwantler et al 1999).…”
Section: Introductionmentioning
confidence: 99%